2022
DOI: 10.1038/s41467-022-35176-7
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic clustering of insulin receptor underlies its signaling and is disrupted in insulin resistance

Abstract: Insulin receptor (IR) signaling is central to normal metabolic control and is dysregulated in metabolic diseases such as type 2 diabetes. We report here that IR is incorporated into dynamic clusters at the plasma membrane, in the cytoplasm and in the nucleus of human hepatocytes and adipocytes. Insulin stimulation promotes further incorporation of IR into these dynamic clusters in insulin-sensitive cells but not in insulin-resistant cells, where both IR accumulation and dynamic behavior are reduced. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 132 publications
0
17
1
Order By: Relevance
“…Synaptophysin (Cell Signaling #5461 (Wu et al., 2018)), NeuN (Cell Signaling #24307 (Tang et al., 2021)), PSD‐95 (post‐synaptic marker, Cell Signaling #36233 (Shui et al., 2022)), Homer‐1 (post‐synaptic marker, SC‐136358 (Wang et al., 2014)), SNAP‐25 (Cell signaling #5308 (Polishchuk et al., 2023)), VAMP2 (Cell signaling #13508 (Arrojo et al., 2019)) were measured as synaptic and neuronal markers. Total IR α (Cell signaling #74118 (Dall'Agnese et al., 2022)), total IR β (Cell signaling #23413 (Dall'Agnese et al., 2022)), IRS1 S636 (Cell signaling #2388 (Uddin et al., 2019)), total IRS1 (Cell signaling #2390 (Tang et al., 2019)), mTOR S2448 (Cell signaling #2971 (Luo et al., 2022)), total mTOR (Cell signaling #2972 (Luo et al., 2022)), Akt T308 (Cell signaling #9275 (Mathieu et al., 2019)), Akt S473 (Cell signaling #4058 (Marko et al., 2020)), and total Akt (Cell signaling #4685 (Marko et al., 2020)) were measured as markers of insulin signaling. Ponceau S, α ‐tubulin (Cell signaling #2144 (Mertins et al., 2021)), GAPDH (Abcam ab8245 (Luo et al., 2023)) or β ‐Actin (Abcam ab8227 (Moll et al., 2023)) were utilized as loading controls.…”
Section: Methodsmentioning
confidence: 99%
“…Synaptophysin (Cell Signaling #5461 (Wu et al., 2018)), NeuN (Cell Signaling #24307 (Tang et al., 2021)), PSD‐95 (post‐synaptic marker, Cell Signaling #36233 (Shui et al., 2022)), Homer‐1 (post‐synaptic marker, SC‐136358 (Wang et al., 2014)), SNAP‐25 (Cell signaling #5308 (Polishchuk et al., 2023)), VAMP2 (Cell signaling #13508 (Arrojo et al., 2019)) were measured as synaptic and neuronal markers. Total IR α (Cell signaling #74118 (Dall'Agnese et al., 2022)), total IR β (Cell signaling #23413 (Dall'Agnese et al., 2022)), IRS1 S636 (Cell signaling #2388 (Uddin et al., 2019)), total IRS1 (Cell signaling #2390 (Tang et al., 2019)), mTOR S2448 (Cell signaling #2971 (Luo et al., 2022)), total mTOR (Cell signaling #2972 (Luo et al., 2022)), Akt T308 (Cell signaling #9275 (Mathieu et al., 2019)), Akt S473 (Cell signaling #4058 (Marko et al., 2020)), and total Akt (Cell signaling #4685 (Marko et al., 2020)) were measured as markers of insulin signaling. Ponceau S, α ‐tubulin (Cell signaling #2144 (Mertins et al., 2021)), GAPDH (Abcam ab8245 (Luo et al., 2023)) or β ‐Actin (Abcam ab8227 (Moll et al., 2023)) were utilized as loading controls.…”
Section: Methodsmentioning
confidence: 99%
“…Downstream signals of PI3K are mediated by multiple serine/threonine (Ser/Thr) kinases, including phosphoinositide-dependent protein kinase 1 (PDK1), AKT, mammalian target of rapamycin complex (mTORC), protein kinase C (PKC), ribosomal protein S6 kinase (S6K), AKT substrate of 160 kDa (AS160) and glycogen synthase kinase 3 (GSK3), which regulate the activity of various transcriptional factors, such as Forkhead box protein O1 (FOXO1), peroxisome proliferator-activated receptors (PPARs), PPARγ coactivator-1 alpha (PGC1α), and sterol regulatory element-binding proteins (SREBPs). These promote the metabolic actions of insulin on glucose, lipid, and mitochondrial metabolism, as well as effects on cell proliferation, differentiation, growth and apoptosis [30][31][32][33][34][35][36][37].…”
Section: Distinct Function Of the Pi3k/akt Signaling Pathway In Diffe...mentioning
confidence: 99%
“…The expansion of fat stores in obesity is often associated with a lowgrade inflammation, caused by the infiltration of pro-inflammatory immune cells [77][78][79], and elevated non-esterified fatty acids serum levels, which both contribute to the development of IR. The FFA-mediated IR involves the activation of the Toll-like receptor 4/nuclear factor kappa B (NFκB) pathway [80], while inhibition of the signaling downstream of the insulin receptor is the primary mechanism of inflammatory IR development [35,79]. The elevated oxidative stress present in obesity is disrupting the insulin receptor clustering that is another mechanism decreasing the insulin sensitivity in adipose and hepatic tissues [35].…”
Section: The Role Of Pi3k/akt Signaling Pathway In Obesity and Obesit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic insulin resistance primarily impairs PI3K-AKT signaling [2]. The relationship between IR levels and insulin resistance is unclear, with some studies reporting reduced IR levels in insulin-resistant states [13]- [16] and others observing no significant differences between insulin-sensitive and insulin-resistant groups [17], [18]. Studies have shown that changes in subcellular localization of IR may play a role in hepatic insulin resistance [17].…”
Section: Introductionmentioning
confidence: 99%